The effect of host age on biological characteristics of Cotesia plutellae - LI Yuan-xi; LIU Shu-sheng (浙江大学学报. 农业与生命科学版)
The effects of larval instars and ages of Plutellae xylostella at initial parasitization on developmental time, rate of cocoon formation, and parasitic capacity of resultant female wasp of Cotesia plutellae, were observed. The results showed that the development of egg and larva of parasitoid initially parasitizing in the 3rd instar larva was faster than development of those initially parasitizing in the 2nd and the 4th instars larvae. The rate of cocoon formation and parasitic capacity of resultant female wasps were also higher in former, indicating that the 3rd instar larva of P. xylostella was more suitable than the 2nd and the 4th instars larvae for C. plutellae, though host age at parasitization had no effect on the emergence rate of parasitoids. In all host instars and ages tested, there were some parasitized individuals that died before the parasitoid larva matured and ate out of the host. For host larvae initially parasitized at the 2nd and the 3rd instars, these deaths occurred mainly during larval development; for those larvae initially parasitized at the 4th instar, many deaths occurred during pupal development. When host larvae were initially parasitized at the 3rd day of the 4th instar, 62.5% of parasitized larvae died at the pupal stage. The relationship between suitability of host age and oviposition preference of parasitoid was also discussed.